Phylogenetic construction of Green Algae Based on the rbcL Gene - Aliarani Rosyidiana Putri; Galuh Arkana; Haikal Ageng Maulana; Septhyanti Aprilia Kavitarna; Rayhan Yugo Nurul Maulana; Muhammad Wisam Wira Sakti; Turhadi Turhadi; Fatchiyah Fatchiyah (JSMARTech: Journal of Smart Bioprospecting and Technology, 2023)
Chlorophyta (green algae) is one of the algae that can be found in (both oceans and freshwater lakes) as well as land with temperate to dry climates. Chlorophyta or green algae can be found in oceans, freshwater lakes, temperate land, and dry climate land.  In addition, chlorophyta can also be found in semi-aquatic environments, such as rocks, moist soil, and moist tree bark. This study aims to analyze the phylogenetic relationship among chlorophyta species based on rbcL gene to classify the diversity of green algae in Indonesia. The green algae gene rbcL sequence with 20 species was obtained from NCBI. The sequences obtained were aligned with ClustalW and the mutation patterns were analyzed. The aligned sequences were made phylogenetic trees by MEGA-X with the Maximum Parsimony method and 1000 bootstrap. The total percentage of transversions that occurred was 10.75%, while the percentage of transitions was 7.85%. The construction of the phylogenetic tree shows that the chlorophyta species are grouped based on their habitat in the same clade. Clad 1 consists of genera Chlorella, Coccomyxa, and Volvox with freshwater habitats and a genus of Parachlorella with soil habitat. Clade 2 consists of genera Chlorococcum, Tetradesmus, Crucigenia, and Desmodesmus with freshwater habitats and a genus of Chlorococcum with soil habitats. Clad 3 consists of genera Ulva and Chlorella salina with marine habitat. The furthest pairwise distance analysis results were shown by Coccomyxa subellipsoidea and Sargassum schnetteri with a value of 1.18902. The kinship of the species of the Chlorophyta division based on the rbcL gene is divided into 3 clade separated by habitat. The phylogenetic tree in the Chlorophyta division shows that the rbcL gene is sensitive enough to separate among genera and can be utilized in phylogenetic studies.